Alteration in plant spacing improves submergence tolerance in Sub1 and non-Sub1 rice (cv. IR64) by better light interception and effective carbohydrate utilisation under stress - Bhaduri, Debarati; Chakraborty, Koushik; Nayak, A.K.; Shahid, Mohammad; Tripathi, Rahul; Behera, Rashmita; Singh, Sudhanshu; Srivastava, Ashish K. (Commonwealth Scientific and Industrial Research Organisation, 2020)
Besides genetic improvement for developing stress-tolerant cultivars, agronomic management may also add considerable tolerance against different abiotic stresses in crop plants. In the present study, we evaluated the effect of six different spacing treatments (S1: 10 × 10 cm; S2: 15 × 10 cm; S3:15 × 15 cm; S4:20 × 10 cm; S5: 20 × 15 cm; S6: 20 × 20 cm (row-row × plant-plant)) for improving submergence tolerance in rice. A high yielding submergence intolerant rice cultivar IR64 was tested against its SUB1 QTL introgressed counterpart (IR64-Sub1) for 12 days of complete submergence for different spacing treatments in field tanks. Relatively wider spaced plants showed higher individual plant biomass and early seedling vigour, which was particularly helpful for IR64 in increasing plant survival (by 150% in S6 over S1) under 12 days of submergence, whereas the improvement was less in IR64-Sub1 (13%). Underwater radiation inside the plant canopy, particularly beyond 40 cm water depth, was significantly greater in wider spacing treatments. Leaf senescence pattern captured by SPAD chlorophyll meter reading and chlorophyll fluorescence imaging data (Fm, Fv/Fm) taken at different time intervals after stress imposition suggested that there was lesser light penetration inside the canopy of closer spaced plants, and that it might hasten leaf senescence and damage to the photosynthetic system. The initial content of total non-structural carbohydrate (NSC) was higher in wider spaced plants of IR64, and also the rate of depletion of NSC was lesser compared with closer spaced plants. In contrast, there was not much difference in NSC depletion rate under different spacing in IR64-Sub1. Further, higher antioxidant enzyme activities in wider spaced plants (both IR64 and IR64-Sub1) after de-submergence indicated better stress recovery and improved tolerance. Taken together we found that wider spacing (row-row: 20 cm and plant-plant: 15 cm and more) can significantly improve submergence tolerance ability in rice, particularly in submergence intolerant non-Sub1 cultivar like IR64, perhaps due to better underwater light penetration, delayed leaf senescence and slower depletion of NSC reserve.